Perancangan Promosi Wisata Pantai Berbasis Videografi Sebagai Upaya Pengenalan Pariwisata Kabupaten Kotabaru Kalimantan Selatan - Ismail, Alban; Martono, Siswo; Latif, Yusmita Akhirul (Jurnal Art Nouveau, 2016)
Kotabaru District is one district in South Kalimantan Province is geographically quite unique, which in addition to having many islands, beaches and oceans as well as most of the island of Borneo also has mountains, valleys and plains as well as the persistence of the forest area or inland. This diversity is raised exotic nature so that it can be used as a tourist attraction. Therefore, as the introduction of South Kalimantan Kotabaru District tourism as well as to promote the tourism sector in Kotabaru, the authors put it in the form of beach-based tourism promotion design videography. The research method uses qualitative methods with data collection technique using observation, interviews, literature, and existing. The concept used in the design is the "beauty". That is the concept of beach tourism Kotabaru district, South Kalimantan has the beauty and uniqueness of each coast. The concept will be applied to any design that includes video and other supporting media. The results of the video and the media promotion of shore excursions are an attempt introduction of tourism in the district of South Kalimantan Kotabaru to attract tourists to visit. Besides promoting coastal tourism that can be enjoyed in various media.Keywords: Design, Video, Travel, Beach, Kotabaru, South Kalimantan, Beauty.